2020
DOI: 10.1097/gox.0000000000003250
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical Correction of Congenital Ear Anomalies: A Review of the Literature

Abstract: Summary Congenital ear anomalies have been known to cause lasting psychosocial consequences for children. Congenital ear anomalies can generally be divided into malformations (chondro-cutaneous defect) and deformations (misshaped pinna). Operative techniques are the standard for correction at a minimal age of 5–7, exposing the children to teasing and heavy complications. Ear molding is a non-operative technique to treat ear anomalies at a younger age. Having been popularized since the 1980s, its use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Encouragingly, ear molding as a non-invasive technique could correct auricular deformities and slight malformations safely and effectively. The molding could be initiated long before the onset of teasing, bullying, and loss of self-esteem ( 23 ). We found some ear molding studies may include several cases of helix adhesion, although these cases were not named helix adhesion, the morphological features of the ear figures indicated that patients were with the helix adhesion deformity ( 1 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, ear molding as a non-invasive technique could correct auricular deformities and slight malformations safely and effectively. The molding could be initiated long before the onset of teasing, bullying, and loss of self-esteem ( 23 ). We found some ear molding studies may include several cases of helix adhesion, although these cases were not named helix adhesion, the morphological features of the ear figures indicated that patients were with the helix adhesion deformity ( 1 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, ear molding offers a surgery‐free opportunity to correct auricular deformations and slight malformations in the neonatal period. This is long before the onset of teasing, bullying, and lowered self‐esteem 3,4 . If corrections are initiated after the time window, however, the total treatment time can be much longer, and the outcomes are less favorable.…”
Section: Introductionmentioning
confidence: 99%
“…However the anomaly carries serious psychosocial repercussions for the child as well as the parents. [4][5][6][7] Regarding timing of surgical correction of the prominent ears, there is universally agreed age of the sufferer. Most of the authorities recommend it to be performed before the age of school going.…”
Section: Introductionmentioning
confidence: 99%